KONVERSI ENERGI CAHAYA MATAHARI MENJADI ENERGI LISTRIK MENGGUNAKAN DIODA SILIKON 6A10 MIC - Retno Wulandari; Maksi Ginting; Antonius Surbakti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
A study has been done on Solar Energy Conversion Into Electrical Energy Using Silicon Diode 6A10 MIC in order to determine electrical energy of diode by varying number of diode that used with and without convex lens. This study used an experimental method that comparing the energy generated from the series and paralel diodes circuits with and without lens, then measuring the intensity of the sunshine by using a simple pylheliometer. Current, voltage, and temperature measurements were performed every 20 minutes from 10:00 to 13:00 during 7 days of observation. In the series and parallel circuits using convex lens produced higher energy than those without convex lens, because of more intensity of solar energy absorbed for the circuit with convex lens. The highest energy obtained from the circuit with convex lens were produced by the series circuits of 10 diodes, with was 30,31x10-2 Joule at 13.00 pm, whereas the highest energy for the circuits without the lens was 14.42 w-2 Joule.